The Effect of Deadlift Training on The Improvement of Defensive Position Performance in Central Java Kabaddi Athletes - Muhammad Ridho Haikal; Fajar Dhias Widya Permana (Journal of Physical Education Health and Sport, 2026)
Kabaddi demands high levels of physical ability, particularly muscular strength, core stability, and endurance, yet the training program remains focused on technical and tactical aspects. The purpose of this study was to look at how deadlift training improved the defensive position performance of Central Java Kabaddi competitors. The study employed a quantitative approach, using a quasi-experimental design with a one-group pretest-posttest design. The study included 30 male Central Java Kabaddi Athletes who played as defenders and were chosen using purposive sampling. The intervention, which took the shape of a deadlift training program, lasted eight weeks and consisted of two sessions per week with an intensity of 70-85% of one repetition maximum (1RM). Defensive position performance was assessed using the Defensive Hold Time (DHT) indicator. Normality tests, paired sample t-tests, and effect size analysis (Cohen’s d) were used to analyse the data. The findings revealed that the average DHT score increased from 3.47 seconds in the pretest to 4.30 seconds in the posttest. The paired sample t-test indicated a significant difference (p < 0.05) between pretest and posttest scores. Additionally, with an effect size of 2.35, deadlift training was shown to have a significant impact on improving performance in Kabaddi athletes. Consequently, we can conclude that deadlift exercises are beneficial for enhancing the defensive skills of Kabaddi athletes.